Application of the 2019 ESC/EAS dyslipidemia guidelines to a Mexican population: evaluating treatment targets for secondary prevention in clinical practice. (14th October 2021) - Laguna Munoz, C I; Reyes Pavon, R; Rodriguez Reyes, H; Perales Rivera, D M; Odin De Los Rios Ibarra, M
Abstract: Introduction: In 2019 the ESC/EAS published the update on their guidelines for the management of dyslipidemias. For patients with prior myocardial infarction or stroke, they recommend achieving an LDL level <55mg/dL as a primary objective, and a non-HDL level <85mg/dL as a secondary target. Objective: To analyze the impact and application that the 2019 ESC/EAS dyslipidemia guideline has on the management of dyslipidemia for secondary prevention. Methods: Using data from a nationwide register in Mexico, a retrospective study was performed, including adult patients from 2018–2020 treated for hyperlipidemia and with prior history of stroke, myocardial infarction, or peripheral artery disease, with at least one follow-up visit. Patients were divided into 2 groups according to their LDL target attainment, furthermore, those with an appropriate LDL target were subdivided into 2 groups according to the attainment of the secondary target. Results: 590 patients were included, the mean age at the last visit was 67 years, 68% were men. The most frequent cardiovascular event was myocardial infarction (75%). The most frequent comorbidity found was obesity (79%). 60% of the sample was on high-intensity statin treatment and 5% received only life-style modifications. When the LDL target attainment was analyzed, only 124 patients (21%) had an adequate control (group 1). Patients in this group had a lower mean age (66±12 vs 67±10), BMI was higher in this group (29 vs 28), meanwhile, blood pressure measurements were slightly lower (systolic 123 vs 126 mmHg, diastolic 73 vs 75 mmHg). They had, however, a higher frequency of comorbidities, such as T2D (46% vs 39%), hypertension (77% vs 73%) and heart failure (26% vs 23%). There were also differences in the pharmacological treatments: in group 1, 58% of the patients were treated with a high-intensity statin (vs 60% in group 2), 24% were treated with a moderate-intensity statin (vs 35% in group 2) and only 16% received a dual treatment strategy with ezetimibe (vs 13% in group 2). Only 8 patients received a PCSK9 inhibitor, and only one of them had an adequate LDL target. When the secondary target attainment was analyzed for patients in group 1, 85% of them had also an adequate control (subgroup 1). Conclusions: The treatment targets from the update on the guidelines, are associated with undertreatment of high-risk patients on secondary prevention. At the current time, less than half of the patients included in this study achieved the optimal target, and only 60% of patients are receiving the appropriate intensity of treatment. There might be different patient-physician related barriers to achieving a good control, one to be considered is the important economic implication of the new pharmacologic options. More studies are required to study the before mentioned barriers and to suggest a proper population-based approach to improve adherence to cardiovascular guidelines for secondary prevention. FUNDunding Acknowledgement: Type of funding sources: None.